2014
DOI: 10.1002/hed.23742
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic pectoralis major muscle flap in prevention of pharyngocutaneous fistula in total laryngectomy after radiotherapy

Abstract: Nonirradiated tissue coverage should be routine in total laryngectomy after RT. PMMF is a good adjunct to prevent pharyngocutaneous fistula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
42
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 23 publications
4
42
1
Order By: Relevance
“…11 In comparison to the deltopectoral flap, two studies conducted in 2006 on 34 and 25 patients reported 21% and 40% complication rates, respectively, 12,13 Pharyngocutaneous fistulae occurred in three of 15 patients (20.0%) in our study when the flap was used for closure of a postlaryngectomy defect. 17 On the other hand, the retrospective study cited above revealed no difference in fistula rates between muscle flaps and fasciocutaneous flaps. According to a large multicenter retrospective study published in 2018 by the microvascular committee of the American Academy of Otolaryngology-Head and Neck Surgery, 14 fistula rates for salvage laryngectomy range from 22% to 39%, all types of reconstruction combined.…”
Section: Discussionmentioning
confidence: 91%
“…11 In comparison to the deltopectoral flap, two studies conducted in 2006 on 34 and 25 patients reported 21% and 40% complication rates, respectively, 12,13 Pharyngocutaneous fistulae occurred in three of 15 patients (20.0%) in our study when the flap was used for closure of a postlaryngectomy defect. 17 On the other hand, the retrospective study cited above revealed no difference in fistula rates between muscle flaps and fasciocutaneous flaps. According to a large multicenter retrospective study published in 2018 by the microvascular committee of the American Academy of Otolaryngology-Head and Neck Surgery, 14 fistula rates for salvage laryngectomy range from 22% to 39%, all types of reconstruction combined.…”
Section: Discussionmentioning
confidence: 91%
“…After evaluating their titles and abstracts, 298 studies were excluded because they clearly did not fill the inclusion criteria. Sixteen articles potentially fit for inclusion in the review were selected . Of these, 4 were excluded after a complete reading: the first was excluded because it did not provide data regarding the incidence of pharyngocutaneous fistula separately between the groups submitted to primary and salvage laryngectomy; the second article referred to the surgical technique description, with no comparative data; the third article presented a case series of patients already mentioned in another study included in this review; in the fourth article, various types of surgical flaps were used precluding the use of data on the PMMF .…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 4 were excluded after a complete reading: the first was excluded because it did not provide data regarding the incidence of pharyngocutaneous fistula separately between the groups submitted to primary and salvage laryngectomy; the second article referred to the surgical technique description, with no comparative data; the third article presented a case series of patients already mentioned in another study included in this review; in the fourth article, various types of surgical flaps were used precluding the use of data on the PMMF . Thus, this review included data from 12 observational retrospective studies, including 742 patients (253 in the PMMF group and 489 in the control group; Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PMMF has been the workhorse flap for this indication. While some studies show a clear reduction in pharyngocutaneous fistula rates, others suggest that the fistulae that occur are smaller and rarely need repair [13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%